Bank lending to targets of active takeover attempts: The simultaneous choice of loan maturity, pricing, and security. Issue 2 (30th July 2019) - Lallemand, Justin
Abstract: I investigate bank loans to takeover targets considering the simultaneous decision of pricing, maturity, collateral, and covenants applying Generalized Method of Moments (GMM). Results are largely in line with the Agency Theory of Covenants (ATC) as pricing for new bank debt is lower given greater collateral and covenant protection, consistent with existing literature on public debt. However, poor performing targets demonstrate a positive relationship between pricing and covenants while bank loans to high performers are consistent with ATC predictions. Finally, loan terms tied to ex post observations of merger outcomes suggest banks possess some knowledge of merger outcomes in advance.